COVID-19 risk groups and their strategies for navigating information overload during the first year of the pandemic in Chile - Verónica Rocamora Villena; Macarena Peña y Lillo; Patricia Junge Cerda; Cecilia Prieto Bravo (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2023)
As a part of the EIS-COVID project on the access and use of information during the COVID-19 pandemic in Chile, the objective of this paper was to ascertain how people's informational environment was constructed during the first stage of the pandemic. It discusses the results of a qualitative study of people belonging to risk groups for COVID-19: people over 18 and under 65 with chronic diseases (hypertension and diabetes) and people 65 and over. Ninety semi-structured interviews were conducted in the Metropolitan and Valparaíso regions between September 2020 and January 2021. The results reveal the problematic nature of the information overload encountered by these groups and the strategies they used to navigate it: a) information avoidance; b) content corroboration and active search for reliable sources; and c) differentiated media use.